PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG, DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS (Studi Empiris Pada Perusahaan Manufaktur Sektor Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2016-2019) - Jadongan Sijabat; Monica Indriyani Sijabat (LPPM Universitas HKBP Nommensen, 2021)
Profitability is the company's ability to earn a profit. One of the factors that can affect the profitability of a company is financial ratio. The purpose of this study was to determine how the influence of Cash Turnover, Accounts Receivable Turnover, and Inventory Turnover on Profitability which will be measured through Return On Assest (ROA) in consumer goods industry manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2019 period. The population in this study is the consumer goods industry sector, which number as many as 53 companies. The sample of this research is 30 companies taken based on purposive sampling technique. This study uses secondary data in the form of corporate financial reports obtained through www.idx.co.id. The data analysis method used is multiple linear regression analysis with a significant level of 5% using SPSS software. The results of this study indicate that partially cash turnover has no significant negative effect on Return on Assets (ROA), accounts receivable turnover has a positive and significant effect on Return on Assets (ROA), inventory turnover has no significant positive effect on Return on Assets (ROA). The results simultaneously explain that cash turnover, accounts receivable turnover, and inventory turnover have a significant effect on ROA in manufacturing companies in the consumer goods industry listed on the Indonesia Stock Exchange. The Adjusted R Square value is 0.560. This means that 56% of profitability is affected by cash turnover, accounts receivable turnover, and inventory turnover. While the remaining 44% is influenced by other factors not examined in this study.